Writing and Reading Skills in Children with Benign Childhood Epilepsy with Centrotemporal Spikes: Systematic Review - Teixeira, Joana; Santos, Maria Emília; Oom, Paulo (Journal of Pediatric Epilepsy, 2022)
In this study, we present the results from a systematic literature review that aimed to gather information about the writing and reading capacities of children with benign childhood epilepsy with centrotemporal spikes. This research comprises studies published between 2005 and 2016 in PubMed, Science Direct, and PsycInfo that included the keywords “benign childhood epilepsy with centrotemporal spikes”/ “rolandic epilepsy” with “written language”/ “reading” / “writing” / “literacy”/ “learning disabilities.” The study selection criteria were: (i) conducted with children with this epileptic syndrome aged between 5:11 and 16; (ii) involving children with active epilepsy or in remission; (iii) assessing written language or learning skills involving reading and writing; and (iv) published in journals with scientific refereeing. From the articles that met all the criteria defined, we compiled and synthesized the information about written language abilities. Reading problems appear to have higher incidence in this population, mostly with regard to the speed and reading accuracy and the ability to comprehend a written text. Fewer limitations were found in writing skills, but some studies showed difficulties in words writing, punctuation/ accentuation, and spontaneous writing coherence and cohesion. We also found disparities in the results regarding the relationship between writing skills and the clinical variables associated with epilepsy. Despite the heterogeneity of this population, it was possible to synthesize and define more precisely the written language variations presented. However, more concrete information is needed about written language disorders in this population, to present valid data to support clinical and pedagogical practices.
Keywords: written language; learning disorders; benign childhood epilepsy with centrotemporal spikes; rolandic epilepsy